2022
DOI: 10.1101/2022.11.09.515757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inclusion of minor alleles improves catalogue-based prediction of fluoroquinolone resistance inMycobacterium tuberculosis

Abstract: Fluoroquinolone resistance poses a threat to the successful treatment of tuberculosis. Whole genome sequencing (WGS), and the subsequent detection of catalogued resistance- associated mutations, offers an attractive solution to fluoroquinolone susceptibility testing. However, the bioinformatic pipelines used often mask the recognition of minor alleles which are implicated in fluoroquinolone resistance. Using the Comprehensive Resistance Prediction for Tuberculosis: an International Consortium's (CRyPTIC) datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Limitations to this study include the lower number of isolates resistant to newer drugs, the lack of isolates from lineages 5 and 6, which are responsible for a significant proportion of cases in sub-Saharan Africa, potential misattribution of mutational effects outside our target genes or due to exclusion of insertions/deletions >50 bp in size from our model, and the use of ECOFFs that have not yet been extensively validated against other methods, although we have shown good concordance with MGIT and MODS results 17 . In addition, it has been shown that minor alleles at sites associated with resistance can influence MIC 55 . While we have tried to limit this effect by removing isolates for which we could not confidently call a variant at a site previously associated with resistance, it is possible that novel resistance-associated sites with minor alleles could affect our model.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to this study include the lower number of isolates resistant to newer drugs, the lack of isolates from lineages 5 and 6, which are responsible for a significant proportion of cases in sub-Saharan Africa, potential misattribution of mutational effects outside our target genes or due to exclusion of insertions/deletions >50 bp in size from our model, and the use of ECOFFs that have not yet been extensively validated against other methods, although we have shown good concordance with MGIT and MODS results 17 . In addition, it has been shown that minor alleles at sites associated with resistance can influence MIC 55 . While we have tried to limit this effect by removing isolates for which we could not confidently call a variant at a site previously associated with resistance, it is possible that novel resistance-associated sites with minor alleles could affect our model.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations to this study include the lower number of isolates resistant to newer drugs, the lack of isolates from lineages 5 and 6, which are responsible for a significant proportion of cases in sub-Saharan Africa, potential misattribution of mutational effects outside our target genes or due to exclusion of insertions/deletions > 50bp in size from our model, and the use of ECOFFs that have not yet been extensively validated against other methods, although we have shown good concordance with MGIT and MODS results 17 . In addition, it has been shown that minor alleles at sites associated with resistance can influence MIC 56 . While we have tried to limit this effect by removing isolates for which we could not confidently call a variant at a site previously associated with resistance, it is possible that novel resistance-associated sites with minor alleles could affect our model.…”
Section: Discussionmentioning
confidence: 99%
“…Other frequent consensus FP calls included fabG1 c-15t, which is associated with ethionamide (n=441) and isoniazid (n=241) resistance, and rrs a1401g, which is associated with resistance to capreomycin (n=241), amikacin (n=70) and kanamycin (n=48). In addition, there were common false positives from gyrA mutations A90V and D94G, which are associated with resistance to the fluoroquinolones levofloxacin (n=108 and n=70, respectively), moxifloxacin (n=419 and n=349) and ofloxacin (n=19 and n=17), and are known to cause heteroresistance and minimum inhibitory concentrations (MICs) close to the critical concentration threshold [56][57][58].…”
Section: Sensitivity and Specificity Performancementioning
confidence: 99%